2013
DOI: 10.1371/journal.pone.0066402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auditory Stimuli in the Horizontal Plane on Audiovisual Integration: An Event-Related Potential Study

Abstract: This article aims to investigate whether auditory stimuli in the horizontal plane, particularly originating from behind the participant, affect audiovisual integration by using behavioral and event-related potential (ERP) measurements. In this study, visual stimuli were presented directly in front of the participants, auditory stimuli were presented at one location in an equidistant horizontal plane at the front (0°, the fixation point), right (90°), back (180°), or left (270°) of the participants, and audiovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…The initial difference between AV and A + V was observed at 180-200 ms over the parietal-occipital areas with ipsilateral auditory stimuli, which was consistent with previous studies [9,15]. However, the latency of the ERP activity in the current study was slightly delayed compared with that reported in a previous study [15].…”
Section: Audiovisual Integration In the Occipital Areas (180-200 Ms)supporting
confidence: 91%
See 1 more Smart Citation
“…The initial difference between AV and A + V was observed at 180-200 ms over the parietal-occipital areas with ipsilateral auditory stimuli, which was consistent with previous studies [9,15]. However, the latency of the ERP activity in the current study was slightly delayed compared with that reported in a previous study [15].…”
Section: Audiovisual Integration In the Occipital Areas (180-200 Ms)supporting
confidence: 91%
“…In contrast, when the visual and auditory stimuli were presented in different locations, little or no enhancement was observed [2,[4][5][6]. Some studies have investigated the effect of unilateral [9] or bilateral auditory stimuli [10] on AV integration with central presentation of visual stimuli and found that significant AV integration is induced by bilateral auditory stimuli rather than by unilateral auditory stimuli [9,10]. Some studies have investigated the effect of unilateral [9] or bilateral auditory stimuli [10] on AV integration with central presentation of visual stimuli and found that significant AV integration is induced by bilateral auditory stimuli rather than by unilateral auditory stimuli [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…2c). Some studies of AV integration reported a similar ERP component in right temporal area but not in left temporal area [15,22]. They hypothesized that the ERP component in the right temporal area is related to AV interaction that originates in the anterior part of the right temporal lobe and/or the inferior lateral prefrontal cortex.…”
Section: Between 300 and 380 Ms Over Temporal Areasmentioning
confidence: 99%
“…Event related potentials are initiated by neuronal mass activity that can generate measurable electric scalp fields in fixed-time relation to an event to find a similar effects of inversion and contrast reversal behaviorally on reflecting various stimuli (Yang et al, 2013). Analyzing the ERPs can serve cognitive purposes in assessing cognitive responses without recognizable performances, but with neurophysiologic activity recorded.…”
Section: Event-related Potentials Processingmentioning
confidence: 99%